The Cab Trade in Winnipeg, 1871–1910 - Beattie, Norman (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1998)
The history of the cab trade in Canada prior to 1914 is a largely unexplored field. This paper outlines the history of cabs in Winnipeg from 1871, when the first livery stables were opened, to 1910, when motorised taxicabs were introduced. The most striking feature of the early cab trade was its unprofitability, stemming the nature of the trade itself and from local conditions that made matters worse. Low revenues, high operating costs, a small and fragmented local market and competition from inside and outside the trade tended to keep individual enterprises small and without sufficient resources to compete with the well-financed taxicab companies that appeared in 1910. The taxicab dealt a severe blow to the horse cab, but the growing numbers of private automobiles also diminished the potential market for both horse cabs and taxicabs. Further, the private automobile created a whole new class of competitors as owners discovered lucrative sidelines in car hire and jitney services.